2020
DOI: 10.1111/jan.14465
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing cardiovascular medication adherence: A medical research council complex mhealth intervention mixed‐methods feasibility study to inform global practice

Abstract: Cardiovascular disease (CVD) is the main reason for mortality worldwide, accounting for more than 17 million deaths each year (World Health Organisation, 2019). In particular, mortality rates caused by CVD are increasing in low-and middle-income countries (World Health Organisation, 2019). Reducing the prevalence, morbidity and mortality of CVD, as the leading cause of the wider burden of non-communicable disease, is a major world health priority (World Health Organization, 2019). In Iran, coronary heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 47 publications
2
22
0
3
Order By: Relevance
“…In addition, the results of the current study revealed positive feedback for the acceptability and usefulness of mHealth intervention to promote cardiovascular diseases in the Iranian setting. This is consistent with the ndings from a systematic review which identi ed that mHealth interventions must be exible as well as culturally and socially appropriate to the desires and needs of the patients (43,44). Anderson (38) found that the knowledge of pathophysiological mechanisms of CSX is still limited for physicians.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In addition, the results of the current study revealed positive feedback for the acceptability and usefulness of mHealth intervention to promote cardiovascular diseases in the Iranian setting. This is consistent with the ndings from a systematic review which identi ed that mHealth interventions must be exible as well as culturally and socially appropriate to the desires and needs of the patients (43,44). Anderson (38) found that the knowledge of pathophysiological mechanisms of CSX is still limited for physicians.…”
Section: Discussionsupporting
confidence: 80%
“…In this regard, the result of a similar study has reported that TextMe2 will generate reliable data about the effectiveness of an entire text message-based intervention as a potential primary prevention solution to control multiple cardiovascular risk factors among those at moderate to high cardiovascular risk (42). Meanwhile, Khonsari, et al nd out that the mHealth intervention had the desired effect on cardiovascular risk factors management and can lead to adherence to medication among Iranian CHD patients (43). The mHealth intervention was well accepted and feasible with early evidence of effectiveness that needs to be con rmed in an entirely in uenced future randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations